EFEKTIVITAS PEMERIKSAAN PAJAK DI INDONESIA - Andri, Muhammad; Winarningsih, Srihadi; Devano, Sony (Universitas Muhammadiyah Palembang, 2021)
The main objective of this study is to examine and measure how much influence the factors that affect the effectiveness of tax audits in Indonesia. The study was conducted with a quantitative approach using multiple regression models. Tax auditor as a party directly involved in the tax audit is a relevant research subject. Cluster sampling technique was used to determine samples. In cluster sampling, the population is divided into clusters based on criteria such as target and realization of work unit acceptance, realization of extra effort and achievement of audit coverage ratio (ACR), so as to represent conditions in the population. The data were successfully collected from 166 tax auditors. The study shows that top management support, taxpayer attitudes and use of taxation information system have significant influence on tax audit effectiveness,while tax regulation and quality of tax audit have no significant influence on tax audit effectiveness.